Software development for prediction of projectiles’ flight path - Aow, Wilson Wei Xian (Nanyang Technological University, 2020)
For a fatal fall case, extensive investigations are conducted to determine the nature of the fall. Fall from height is often uncertain whether the mode of death is suicide, accident, or homicide. If foul play is involved in a fatal fall, the police should gather as much supporting evidence as possible within the shortest time, to apprehend the perpetrator. The flight path of a falling human body is closely related to a projectile motion used in kinematics physics. A retrospective analysis of injury patterns was used to assess and differentiate the fall victims from a jump, accidental fall, or suicide. A user-friendly window application is created to provide predictions of different situations for all levels in the building. The program has two functions. Based on the victim’s age, mass, height, gender, building maximum floor, and the horizontal distance between building and victim’s centre of mass. It calculates and provides different possibilities of foul play for all levels in the building. Next, using an official autopsy report with injuries details to shortlist the range of possible launching height. A user’s guide is provided on the instruction on how to use these features. Experiments are conducted to verify the accuracy of the prediction by the program. The results were compared and displayed an accuracy level of 92.68%. Results also show that all the test cases might be voluntary or accidental.